Tax arbitrage in the German insurance market - Andreas Richter; Jochen Ruß (Hamburg University, Institute for Risk and Insurance, 2001)
In this paper we analyze the attractiveness of a so called mortality swap, which combines an immediate annuity and a whole life insurance contract, in the German insurance market. The analysis follows a methodology introduced by Charupat and Milevsky (2001). Using theoretical products based on actuarially fair calculation, we find that depending on the level of interest rates there exist significant arbitrage opportunities in particular for elderly and high income people which can mainly be explained by an inadequate and unsatisfactory tax legislation. Empirical results based on products offered in the market confirm these findings.
Keywords: 330